Association of Four Medication Classes and Non-suicidal Self-injury in Adolescents with Affective Disorders – A Retrospective Chart Review - Eggart, Vincent; Mortazavi, Matin; Kirchner, Sophie-Kathrin; Keeser, Daniel; Brandstetter, Lisa; Hasan, Alkomiet; Wagner, Elias (Pharmacopsychiatry, 2023)
Background Non-suicidal self-injury (NSSI) behaviour is frequently observed in children and adolescents with psychiatric conditions. Affected individuals are regularly treated with psychotropic drugs, although the impact of these agents on NSSI behaviour remains elusive.Methods We performed a retrospective chart review from clinical routine data in a large cohort (N=1140) of adolescent inpatients with primary affective and non-affective psychiatric disorders according to ICD-10 (mean age=15.3±1.3 years; 72.6% female). Four separate mixed regression models compared the frequency of NSSI between treatment periods without any medication and four medication categories (benzodiazepines, selective serotonin reuptake inhibitors (SSRIs), high- and low-potency antipsychotics).Results In those individuals with affective disorders as the primary diagnosis, periods without medication were associated with significantly lower NSSI/day compared to all four other medication conditions (benzodiazepines p<10−8, antidepressants/SSRIs p=0.0004, high-potency antipsychotics p=0.0009, low-potency antipsychotics p<10 −4). In individuals with a primary diagnosis other than an affective disorder, NSSI was significantly lower during the period without medication compared to the treatment periods with benzodiazepines (p=0.005) and antidepressants/SSRIs (p=0.01). However, NSSI rates in the no-medication condition were comparable to NSSI rates under high-potency (p=0.89) and low-potency antipsychotics (p=0.53).Conclusions The occurrence of NSSI correlates with the treatment with a psychotropic drug in children and adolescents with psychiatric disorders. Due to the retrospective design, it remains elusive to what extent psychotropic drugs might alter the frequency of NSSI in adolescents or if NSSI might indicate a transdiagnostic feature of more pronounced disease severity.
Keywords: non-suicidal self-harm; benzodiazepine; adolescents